Cross-Game Learning and Cognitive Ability in Auctions - Thomas Giebe; Radosveta Ivanova-Stenzel; Martin G. Kocher; Simeon Schudy (Center for Economic Studies and ifo Institute (CESifo), 2021)
Overbidding in second-price auctions (SPAs) has been shown to be persistent and associated with cognitive ability. We study experimentally to what extent cross-game learning can reduce overbidding in SPAs, taking into account cognitive skills. Employing an order-balanced design, we use first-price auctions (FPAs) to expose participants to an auction format in which losses from high bids are more salient than in SPAs. Experience in FPAs causes substantial cross-game learning for cognitively less able participants but does not affect overbidding for the cognitively more able. Vice versa, experiencing SPAs before bidding in an FPA does not affect bidding behavior by the cognitively less able but, somewhat surprisingly, reduces bid shading by cognitively more able participants, resulting in lower profits in FPAs. Thus, cross-game learning has the potential to benefit bidders with lower cognitive ability whereas it has little or even adverse effects for higher ability bidders.
Keywords: C72; C91; D44; D83; 330; cognitive ability; cross-game learning; experiment; auction; heuristics; first-price auctions; second-price auctions